Design and Application of Quantified Self Approaches for Reflective Learning in the Workplace (2015)
Learning by reflection is one of the core processes for improving work performance. We provide a novel approach for reflective learning support by transferring and adapting practices from the Quantified Self to workplace settings. This book contributes with an integrated model for technical support of reflective learning, mobile and web-based applications designed for quantifying and gathering data in the workplace, and empirical insights from thirteen studies in three different use cases.